Retrotransposon gag-like 1 (RTL1) and the molecular evolution of self-targeting imprinted microRNAs - Avantika Mainieri; David Haig (Biology Direct, 2019)
Abstract Background Transcription of the antisense strand of RTL1 produces a sense mRNA that is targeted for degradation by antisense microRNAs transcribed from the sense strand. Translation of the mRNA produces a retrotransposon-derived protein that is implicated in placental development. The sense and antisense transcripts are oppositely imprinted: sense mRNAs are expressed from the paternally-derived chromosome, antisense microRNAs from the maternally-derived chromosome. Results Two microRNAs at the RTL1 locus, miR-431 and the rodent-specific miR-434, are derived from within tandem repeats. We present an evolutionary model for the establishment of a new self-targeting microRNA derived from within a tandem repeat that inhibits production of RTL1 protein when maternally-derived in heterozygotes but not when paternally-derived. Conclusions The interaction of sense and antisense transcripts can be interpreted as a form of communication between maternally-derived and paternally-derived RTL1 alleles that possesses many of the features of a greenbeard effect. This interaction is evolutionary stable, unlike a typical greenbeard effect, because of the necessary complementarity between microRNAs and mRNA transcribed from opposite strands of the same double helix. We conjecture that microRNAs and mRNA cooperate to reduce demands on mothers when an allele is paired with itself in homozygous offspring. Reviewers This article was reviewed by Eugene Berezikov and Bernard Crespi.